Heat-tolerant maize for rainfed hot, dry environments in the lowland tropics: from breeding to improved seed delivery - Zaidi, Pervez Haider; Vinayan, Madhumal Thayil; Nair, Sudha K.; Kuchanur, Prakash H.; Kumar, Ramesh; Singh, Shyam Bir; Tripathi, Mahendra Prasad; Patil, Ayyanagouda; Ahmed, Salahuddin; Hussain, Aamir; Kulkarni, Atul Prabhakar; Wangmo, Passang; et al. (Elsevier, 2023)
Climate change-induced heat stress combines two challenges: high day- and nighttime temperatures, and physiological water deficit due to demand-side drought caused by increase in vapor-pressure deficit. It is one of the major factors in low productivity of maize in rainfed stress-prone environments in South Asia, affecting a large population of smallholder farmers who depend on maize for their sustenance and livelihoods. The International Maize and Wheat Improvement Center (CIMMYT) maize program in Asia, in partnership with public-sector maize research institutes and private-sector seed companies in South Asian countries, is implementing an intensive initiative for developing and deploying heat-tolerant maize that combines high yield potential with resilience to heat and drought stresses. With the integration of novel breeding tools and methods, including genomics-assisted breeding, doubled haploidy, field-based precision phenotyping, and trait-based selection, new maize germplasm with increased tolerance to heat stress is being developed for the South Asian tropics. Over a decade of concerted effort has resulted in the successful development and release of 20 high-yielding heat-tolerant maize hybrids in CIMMYT genetic backgrounds. Via public–private partnerships, eight hybrids are presently being deployed on over 50,000 ha in South Asian countries, including Bangladesh, Bhutan, India, Nepal, and Pakistan.